KETERLIBATAN PEREMPUAN DALAM MUSRENBANGKEL DI KELURAHAN KARANGREJO BANYUWANGI (Studi tentang Hambatan dan Upaya Peningkatan Partisipasi Perempuan) - Ika Ayu Lestari; Leni Vitasari; Erna Agustina (Lembaga Penerbit Sekolah Tinggi Hindu Dharma Klaten, 2025)
This study aims to analyze women's participation in the Kelurahan Development Planning Meeting (Musrenbangkel) in Karangrejo Village, Banyuwangi. Using a descriptive qualitative approach, this study identifies barriers that hinder women's involvement and identifies strategies that can be taken to increase their participation. The findings show that although women's presence in the Musrenbangkel forum is becoming more visible, their level of involvement is still low, at only around 30% of the total participants. The main inhibiting factors include social and cultural norms, limited access to information, and the double burden of being both a housewife and a worker. In addition, the dominance of men in the forum and the lack of a gender-friendly facilitation approach also contributed to the low active participation of women. Based on these results, this study recommends the need for concrete actions such as the provision of accessible information, training to increase women's capacity, and the application of more inclusive facilitation methods to create spaces that encourage women's involvement in the development process at the kelurahan level.